Current and Voltage Analysis of the Influence of Capacitors on Electrical Loads - Yusnidah Yusnidah (Jurnal Penelitian Pendidikan IPA, 2023)
Currently, electricity utilization is increasing along with the increasing demand for new tides. Electricity usage increases with demand. When installing power capacitors in the electrical network, it is the installation of capacitors in parallel in an electrical installation in the hope of increasing the efficiency of the power factor. This study aims to determine the effect of capacitors on current and voltage. The method used is an experimental method with the aim of knowing the effect of a treatment. The research design carried out by designing power capacitors, determining the load point of installing power capacitors with 2 electrical loads, namely freezers and fans. Next after the installation of the power capacitor is the measurement of the electrical parameters studied. The results of this study show that the addition of power capacitors has an influence on electrical loads. The average voltage and current values in the fan are 210.6 V and 0.97 A, while in the freezer it is 209.5 and 1.105 A.